KEARIFAN LOKAL DALAM PENGELOLAAN SUMBER DAYA HUTAN DI KABUPATEN SERAM BAGIAN BARAT, KECAMATAN HUAMUAL BELAKANG (STUDI KASUS DI NEGERI BUANO UTARA) - Akin Sombalatu; Evelin Parera; Husein Marasabessy (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Indonesia, as an archipelagic state, possesses abundant natural resources and high biological diversity, including extensive forest ecosystems that vary across regions. Maluku is one of the provinces characterized by vast tropical forests with significant ecological value, while also providing economic benefits for local communities through non-timber forest products such as cajuput oil, copal, rattan, and agarwood. However, these forests face increasing threats from land-use change, particularly due to mining and plantation expansion. In this context, Indigenous communities play a crucial role in sustaining forest resources through customary practices and local wisdom passed down across generations. This study aims to identify forms of local wisdom in forest resource management and examine the factors influencing these practices in Buano Utara Village, Huamual Belakang Subdistrict, West Seram Regency. The research was conducted in May 2025 using a survey method with a descriptive approach to systematically and accurately describe the socio-cultural conditions and forest management practices observed in the field. The results show that the people of Buano Utara regard local wisdom as an essential cultural heritage that shapes their approaches to forest and agricultural resource management. Customary systems such as sasi hutan function effectively in promoting forest sustainability by regulating periods of restricted exploitation, implementing adat-based monitoring, and enforcing sanctions for violators. Local wisdom not only contributes to ecological conservation but also strengthens social cohesion and community resilience. Therefore, local wisdom remains a highly relevant and effective traditional mechanism for supporting sustainable forest resource management in Maluku.